Is distributed leadership an effective approach for mobilising professional capital across professional learning networks? Exploring a case from England. Issue 1 (3rd November 2020) - Brown, Chris; Flood, Jane; Armstrong, Paul; MacGregor, Stephen; Chinas, Christina
Abstract : Purpose: There is currently a focus on using networks to drive school and school system improvement. To achieve such benefits, however, requires school leaders actively support the mobilisation of networked-driven innovations. One promising yet under-researched approach to mobilisation is enabling distributed leadership to flourish. To provide further insight in this area, this paper explores how the leaders involved in one professional learning network (the Hampshire Research Learning Network) employed a distributed approach to mobilise networked learning activity in order to build professional capital. Design/methodology/approach: A mixed methods approach was used to develop a case study of the Hampshire RLN . Fieldwork commenced with in-depth semi-structured interviews with all school leaders of schools participating in the network and other key participating teachers (12 interviews in total). A bespoke social network survey was then administered to schools (41 responses). The purpose of the survey was to explore types of RLN-related interaction undertaken by teachers and how teachers were using the innovations emerging from the RLN within their practice. Findings: Data indicate that models of distributed leadership that actively involves staff in decisions about what innovations to adopt and how to adopt them are more successful in ensuring teachers across networks: (1) engage with innovations; (2) explore how new practices can be used to improve teaching and learning and (3) continue to use/refine practices in an ongoing way. Originality/value: Correspondingly we argue these findings point to a promising approach to system improvement and add valuable insight to a relatively understudied area.